Properties of linear entropy of the atom in a tripartite cavity-optomechanical system. (13th April 2016) - Liao, Q H; Nie, W J; Xu, J; Liu, Y; Zhou, N R; Yan, Q R; Chen, A; Liu, N H; Ahmad, M A
Abstract: We investigate the dynamics of linear entropy of an atom in a tripartite cavity-optomechanical system consisting of a two-level atom in a high-finesse optical cavity with a vibrating mirror at one end. The influence of atomic coherence on the time evolution of linear entropy is examined. It is shown that a Greenberger–Horne–Zeilinger like state can be generated. Moreover, it is found that the entanglement between the atom and the subsystem of field and mirror can be controlled by atomic coherence and the parameters of optomechanical coupling coefficient and atom-field coupling strength.